Performance Evaluation of Palm Oil-based Grease for Wear and Vibration Control in Spur Gears - Adzlan Abu Hasan; Nadiah Aqilahwati Abdullah; Mohd Yusof, Nurul Farhana (International Journal of Integrated Engineering, 2025)
The reliability and efficiency of gear systems are critically dependent on effective lubrication, which minimizes friction and wear between gear teeth. While conventional mineral-based greases are widely used, growing environmental concerns and the demand for renewable alternatives have prompted interest in sustainable lubricants. The formulation of palm oil-based grease and its application in gear systems remain underexplored, particularly regarding tribological performance under dynamic operating conditions. This study addresses this gap by fabricating a custom gear test rig to investigate the surface wear and vibration characteristics of spur gears lubricated with palm olein-based grease enhanced with molybdenum disulfide (MoS₂) nanoparticles. The experiment was conducted with an applied torque of 0.31 Nm, operating at 300 rpm for 240,000 cycles. Lubrication performance was assessed through surface wear analysis using Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS), while vibration data were collected after 240,000 gear cycles using a data acquisition system. The formulated grease PG was benchmarked against a commercial mineral-based grease. Results indicate that the MoS₂ enhanced palm oil grease exhibits superior tribological behavior, with very small mass loss of 6.28x10-2 %, indicating low surface wear. The grease exhibited moderate vibration levels at 0.8 m/s², performing better than mineral grease MG1 and slightly less effectively than MG2 in suppressing gear vibration. EDS analysis confirmed the presence of MoS₂ elements on the worn gear surfaces, indicating effective film formation and adherence. These findings highlight the potential of palm oil-based grease as a sustainable alternative for gear lubrication, offering superior wear resistance and lower vibration levels for better operational efficiency.